2017
DOI: 10.1073/pnas.1705882114
|View full text |Cite
|
Sign up to set email alerts
|

Structural determination of lipid antigens captured at the CD1d–T-cell receptor interface

Abstract: Glycolipid antigens recognized by αβ T-cell receptors (TCRs) drive the activation of invariant natural killer T (iNKT) cells, a specialized subset of innate T lymphocytes. Glycolipids with α-linked anomeric carbohydrates have been identified as potent microbial lipid antigens for iNKT cells, and their unusual α-anomeric linkage has been thought to define a “foreign” lipid antigen motif. However, mammals use endogenous lipids to select iNKT cells, and there is compelling evidence for iNKT cell responses in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…In order to gain structural insights into the molecular recognition of AH10-7 in comparison to KRN7000, we generated complexes in vitro of mCD1d loaded with these glycolipids and co-crystallized them with the 2C12 i NKT cell T (Brennan et al, 2017; Pellicci et al., 2009; Wang et al, 2010) We used X-ray crystallography to determine the 3-dimensional structures of these ternary complexes to 3.2 Å resolution for AH10-7 and 2.6 Å for KRN7000 (Figure 5A, and Supplemental Table 1). In both complexes, the electron density at the molecular interface between the mCD1d-glycolipid complexes and the 2C12 i NKT TCR was unambiguous.…”
Section: Resultsmentioning
confidence: 99%
“…In order to gain structural insights into the molecular recognition of AH10-7 in comparison to KRN7000, we generated complexes in vitro of mCD1d loaded with these glycolipids and co-crystallized them with the 2C12 i NKT cell T (Brennan et al, 2017; Pellicci et al., 2009; Wang et al, 2010) We used X-ray crystallography to determine the 3-dimensional structures of these ternary complexes to 3.2 Å resolution for AH10-7 and 2.6 Å for KRN7000 (Figure 5A, and Supplemental Table 1). In both complexes, the electron density at the molecular interface between the mCD1d-glycolipid complexes and the 2C12 i NKT TCR was unambiguous.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that iNKT cells and DEC‐205 + DCs are accumulated in the decidua of women without aCAM who undergo late preterm birth . Various foods, herbal medicines, and drugs contain glycolipid antigens . Moreover, certain alarmins, HMGB1, uric acid, IL‐1α, and cell‐free DNA may be associated with the onset of pregnancy complications, miscarriages, preeclampsia, and preterm birth through the sterile pathway .…”
Section: Discussionmentioning
confidence: 99%
“…The a-anomeric configurationi sn oteworthy,a s the b-configuration is ac haracteristic feature of most mammalian glycolipids. [3] The mode of action of a-GalCer relies on ah igh-affinity bindinge ventw ith CD1d, am ajor histocompatibility complex (MHC)c lass I-like non-polymorphic glycoprotein associated with the membrane of antigen presenting cells (APCs). This binary a-GalCer-CD1d complex is presented to the semi-invariant ab T-cell receptor (TCR) of invariant natural killer T-cells (iNKT), ad istinct population of CD1d-restricted T-lymphocytes, to form at ernaryc omplex.…”
Section: Introductionmentioning
confidence: 99%
“…The α-anomeric configuration is noteworthy, since the β-configuration is a characteristic feature of most mammalian glycolipids. 3…”
Section: Introductionmentioning
confidence: 99%